Soft Multifunctional Porous Sponge Sensor for Pressure and Strain Using Liquid Metal/Polydimethylsiloxane with Silver-Nanowire-Coated Composite - Dong-Young Kim; Kun-Woo Nam; Byung-Ho Kang; Sung-Hoon Park (Micromachines, 2022)
Compression and tension sensors with a porous structure have attracted attention recently. Porous sponge sensors have the advantage of a wide deformation range owing to their structural characteristics. In this study, a porous sponge structure was prepared by absorbing polydimethylsiloxane (PDMS) into the matrix of porous commercial sugar cubes. A conductive network was formed by coating the outside of the sponge skeleton with silver nanowires (AgNWs), which have a high aspect ratio. In addition, a liquid metal (LM), which does not directly form an electrical network but changes from zero-dimensional to one-dimensional under an external force was introduced into this porous sponge structure. The effects of the LM on the sensor sensitivity to pressure and strain were analyzed by comparing the electrical resistance changes of PDMS/AgNW and LM/PDMS/AgNW sponge sensors under tension and pressure. This study shows that the use of a porous structure and an LM may be useful for future wearable sensor design.